Pengaruh Layanan Informasi Karir dengan Metode Bimbingan Kelompok Terhadap Kesiapan Kerja Siswa Kelas X pada SMK Swasta di Kota Klaten - Ary Ani, Arum Dhita, Dr. Wiwien Dinar Pratisti M.Si (2017)
Work preparedness is a condition which reveals the harmony between the physical mature, mental mature and experience, therefore, an individual has a capability to perform a certain activity in relation to a work. Graduates from vocational high school (SMK) are the biggest contributor of workers which are not well prepared because many companies complained on the workers graduated from vocational high school that the graduates are unable to have achievement and work in team, impolite manner and being arrogant. In order to reach a qualified education, a counseling is necessary in facing the problem. Such guidance in the form of career guidance information services, one of the methods that can be used is group guidance. Group counseling is a counseling service which enables the students collectively through a group dynamic to obtain many guidance from the counsellor teachers in order to take decision in the problem of children moral development individually using the existing facilities. The purpose of this research is to know the influence Career information guidance services by methods of Group Counseling on the Work Preparedness of the 10th Grade Student of Vocational High School. Subjects of this research are as many as 39 which were divided into an experiment group and a control group with characteristics of students with a medium level of work preparedness and low level of work preparedness. The method of this research used an experimental method of pretest post-test control group design. the results of this research were analyzed using tested using independent sample t-test which obtained the value of t = -5.234 with a significance level (p)= 0,000 that means that there is an the influence of group counseling on the work preparedness of the 10th grade students of vocational high school in klaten city.